Integrating Video Blog in EFL Class For Teaching Speaking at SMAN 4 Kendari - Astriani, Ayu; Lio, Asrun; Badara, Aris (Halu Oleo University, 2017)
This research is aimed to investigate the use of video blog in teaching speaking at the first graders. The researcher used quantitative and qualitative data to investigate the utilization of video blog embedding students’ fluency in speaking skill. There are three research questions accomplished in this study: 1. To what extent does Vlog help foreign language English speakers improve their speaking fluency? 2. What are students’ opinion about using Vlog in performing speaking? 3. What are students’ suggestion and feedback about using Vlog in performing speaking? This study was conducted in SMAN 4 Kendari at grade X students who are registered in academic year of 2016/2017. The total number of students involved were 39 for both experiment and control class. The sample was taken using purposive sampling for experimental and control class. The instrument of data collection were speaking test, speaking activity and interview. The speaking test was collected by administering pre test to know the students prior speaking skill, treatment which integrating video blog in the teaching and learning process, and post test to find out what improvement happenned on students’ speaking skill in term of fluency. The result shows the significant difference of experiment and control class. The researcher used independent sample t-test in comparing improvement in experiment and control class. Students’interview result also shows how integrating video blog affect their speaking skill, as the additional data to support the speaking test result